Makna Kehadiran, Paham dan Model Gerakan Keagamaan Muhammadiyah - zaini, moh; Bachrul Ulum; Wiwik Kusmawati; Reno Siska Sari (Universitas Insan Budi Utomo, 2025)
This study examines the presence of the meaning, understanding and model of the Muhammadiyah religious movement. This mass organization has quite a large influence, especially in Indonesia. Founded by K. Ahmad Dahlan on November 18, 1912, with an important goal, namely: Upholding and Upholding the Islamic Religion so that a True Islamic Society is Realized. This paper focuses on the concept of the meaning of the presence, understanding and model of the Muhammadiyah religious movement. This study uses a type of library research, data collection is carried out by collecting various relevant sources of information, related to notes, papers, books, news, articles, to public journals, conducting analysis with a content analysis model, describing in depth, until finally drawing valid conclusions from various sources of documents studied. The results of the study show that the presence of Muhammadiyah is not just a religious organization, but as a socio-transformational movement that instills Islamic values ​​substantially into the structure of society. Its moderate and progressive religious understanding, as well as its movement model based on service and empowerment, make Muhammadiyah an important entity in the formation of the face of progressive Indonesian Islam and presenting His Grace to the universe.